Conclusions as components of research articles across portuguese as a native language, english as a native language and english as a foreign language: a contrastive genre study - Moritz, Maria Ester W.; Meurer, J. L.; Dellagnelo, Adriana Kuerten (The ESPecialist, 2011)
The present study is a contrastive investigation of conclusions of research articles (RAs) written in Portuguese as a native language, English as a native language and English as a foreign language. The analysis was carried out according to the principles of genre studies as proposed by Swales (1990). The corpus is composed of 36 conclusions of RAs in the field of applied linguistics. The findings reveal no constant pattern of rhetorical organization and no obligatory moves or steps. However, the results indicate the occurrence of a complex array of moves and steps which exhibits a cyclical structure but with differences in the three languages investigated. Furthermore, the samples investigated permitted the elaboration of a proposal of a model for this component of RAs. The study, therefore, contributes to a richer understanding of the nature of conclusions of RAs and, as such, of academic writing.